Sử dụng Facebook để kết nối với người sử dụng ở các thư viện Việt Nam - Nguyễn, Thị Hạnh (Cục Thông tin khoa học và công nghệ quốc gia, 2023)
Facebook is a social network, that developed globally. Statistical data shows that until October 6th, 2013, there were 1,2 billion Facebook users. Immediate contact, interactive and free benefits of Facebook are creating great opportunities for individuals and organizations in all fields to connect and share information each other. Libraries in the world have been using Facebook as a tool for connecting with users and publicizing library services since 2007 while in Vietnam, these activities have not been paid enough attention to in library community; This article reviews the development of Facebook, analyzes its benefits for libraries and briefs the usage of this tool in libraries of the world; Based on analyzing success and limitation of Facebook at 12 libraries through a qualitative study, the author puts forward some recommendations on creating and operating an effective Facebook page for libraries.